Facies mapping of the Vaal Reef placer as an aid to remnant pillar extraction and stope width optimisation - O'Donovan, Anthony Gareth (Rhodes University, Faculty of Science, Department of Geology, 1992)
The Vaal Reef placer is situated on the unconformable junction of the Strathmore and Stilfontein formations of the Johannesburg Subgroup. Within the South Division of the Vaal Reefs Exploration and Mining company lease, the Vaal Reef Placer is shown to be composed of several different units. Each unit exhibits its own specific characteristics and trend direction which can be used to establish distinct "Reef packages". These packages can be mapped in such a way as to provide a preliminary lithofacies map for the Vaal Reef Placer. The delineation of such geologically homogenous zones, and the development of a suitable depositional model, can be utilised in several ways. The characteristics of a particular zone are shown to influence the control of stoping width, evaluation of remnant pillars and the geostatistical methodology of evaluating current and future ore reserve blocks.
Keywords: Facies (Geology) -- South Africa -- Vaal Reef placer